Telaah Ontologis Penderitaan Menurut Rasul Paulus : Refleksi Teologis Filipi 1:27-30 - John Marlin (STT Kingdom, 2023)
Suffering is inherent in the dynamics of the Church's historical life, both personal and communal. The correct meaning of suffering in the perspective frame of the truth of the word can strengthen and strengthen the living of faith. In the Bible, suffering has also become part of the struggle of Christians in spreading the good news. However, many times, questions arise from Christians about the existence of suffering and why we have to experience it. The purpose of this paper is to try to interpret and understand suffering based on the Apostle Paul's view taken from the Apostle Paul's letter to the Philippians. The approach taken is the Ontological Approach with the Hermeneutic-Exegesa Method